Effect of Systemic Intraoperative Heparin Use on Upper Extremity Arteriovenous Fistula Patency in End-Stage Renal Disease Patients - Morwan Bahi (The Scientific World Journal)
The formation of the arteriovenous fistula is an important method of vascular access for patients with end-stage renal disease (ESRD). This allows renal filtration resulting in improved life quality and expectancy for ESRD patients. The biggest drawback to arteriovenous fistula formation is thrombosis, which can occur at an early or delayed stage. One suggested method of reducing postoperative arteriovenous fistula thrombosis rates is the administration of intraoperative systemic heparin. Heparin use in this context is debated, and there is currently no consensus on its use. There are a number of small randomised control studies trialling use of heparin but no large systematic trials. In this report, we collate existing evidence in the form of a review article and attempt to extrapolate a consensus of the evidence.